Morphology and dimensions of the thoracic cord by computer-assisted metrizamide myelography. - Gellad, F; Rao, K C; Joseph, P M; Vigorito, R D (American Journal of Neuroradiology, 1983)
Computed tomographic (CT) measurements of the thoracic spine and its contents were obtained in 33 patients undergoing metrizamide myelography for various spinal disorders. Twenty-eight of these patients had symptoms referable to the cervical or lumbar region and form the basis of this study. Five patients had symptoms referable to the thoracic spine. Sagittal and coronal CT measurements of the thoracic cord and subarachnoid space were obtained in all cases. In addition, macroscopic measurements of the thoracic cord were obtained from 10 autopsies for correlation with the CT findings. The technical aspects of the measurements are discussed; the normal morphology of the thoracic cord and thecal sac is presented; and the metrizamide CT pattern associated with pathologic lesions involving the thoracic cord is analyzed.